2011
DOI: 10.1108/00242531111100568
|View full text |Cite
|
Sign up to set email alerts
|

Inter‐organizational knowledge transfer needs among small and medium enterprises

Abstract: Purpose -The purpose of this paper is to build upon Chen et al.'s work by investigating inter-organizational knowledge transfer needs and practices among small and medium enterprises (SMEs) which have received relatively little research attention to date. Design/methodology/approach -A questionnaire survey was conducted on SMEs which have been accorded the Multimedia Super Corridor Malaysia status. Data were analyzed using Statistical Package for the Social Sciences. Findings -In total, nine important areas ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(40 citation statements)
references
References 56 publications
3
35
0
1
Order By: Relevance
“…However, this involves not only the creation of new knowledge from scratch but also the reconfiguration of existing pieces of knowledge to create new knowledge (Lynn et al, 1996). On this issue, Chong et al (2011) found that employees who work together in a team are more efficient at creating new knowledge. Similarly, brainstorming sessions are also found to be effective for generating new ideas (Hutchinson & Quintas, 2008).…”
Section: Knowledge Creationmentioning
confidence: 99%
See 1 more Smart Citation
“…However, this involves not only the creation of new knowledge from scratch but also the reconfiguration of existing pieces of knowledge to create new knowledge (Lynn et al, 1996). On this issue, Chong et al (2011) found that employees who work together in a team are more efficient at creating new knowledge. Similarly, brainstorming sessions are also found to be effective for generating new ideas (Hutchinson & Quintas, 2008).…”
Section: Knowledge Creationmentioning
confidence: 99%
“…Arnold et al (2000) have suggested that firms should encourage collaborative problemsolving and provide opportunities for employees to share their tacit knowledge with each other. Therefore, organizations should arrange meeting sessions where employees are free to share their knowledge, ideas, and information with others (Coyte et al, 2012), as well as promote informal faceto-face social interactions to encourage the sharing of tacit knowledge (Chong et al, 2011). The evidence in the literature so far suggests that it is harder to share knowledge within public sector organizations because most people associate knowledge with power and potential promotion opportunities (Liebowitz & Chen, 2003).…”
Section: Knowledge Sharingmentioning
confidence: 99%
“…Thus, it is not surprising that most of the practices are oriented toward the management of tacit knowledge. Some authors [16,21,[74][75][76][77][78][79][80][81][82] suggest a variety of people-centered practices such as: Focus groups, formal meetings, communities of sharing, virtual communities, informal networks, project teams, interactions with clients, interactions with suppliers, interactions with partners, communities of practices, job rotation, training. Moreover, even though Hutchinson and Quintas (2008) [83] underline that small firms are more likely to adopt informal processes to manage knowledge, other authors [84][85][86][87][88] also suggest the importance of more formal techniques and methods (such as: casual mapping, knowledge maps, balance scorecards, formal manuals), while others suggest establishing a chief knowledge officer [78] or a project team [80,89].…”
Section: Systems Supporting Knowledge Management In Smesmentioning
confidence: 99%
“…Meanwhile, innovation and new ideas come from factors within and outside an organization [2] [3]. This paper focused on the internal view of organization as an organization coaching.…”
Section: Introductionmentioning
confidence: 99%